The link between the shadow economy and the happiness economy in EU euro area countries - Karazijienė, Žaneta; Černikovaitė, Miglė Eleonora; Kazlauskienė, Eglė (Business, Management and Economics Engineering, 2025)
Purpose – the aim of this study is to assess the relationship and influence between the shadow economy and the level of happiness in the Euro area economies of the European Union by highlighting the theoretical assumptions behind the concept and expression of the shadow economy and happiness. Research methodology – to calculate the size of the shadow economy will be used Gutmann’s index. To calculate the happiness of the economies will used the Happiness Economy Index from the World Happiness Report (2022) including the following 6 indicators (GDP per capita, healthy life expectancy (that derives to life expectancy and mental health evaluation), social support, freedom index, generosity (do-nations to charity), and corruption index. To determine the relationship between the shadow and happiness economy, the Granger causality method. Research limitations – the study’s limitations include data reliability and accuracy, methodological limitations, geographical and cultural differences, and time constraints. The estimation of the size of the shadow economy and the happiness economy index may contain inaccuracies, and the Granger causality method cannot fully confirm causality. The study is limited to the euro area countries of the European Union; therefore, the results may not be fully applicable to other countries. Additionally, the data may not fully capture long-term trends or developments. Practical implications – the results of this study can help policymakers and economists better understand how to reduce the size of the shadow economy and thereby increase people’s happiness. The study’s findings indicate a positive correlation between a country’s Happiness Economy Index and the size of its shadow economy. This suggests that investing in people’s well-being can positively impact the formal economy. Furthermore, the study’s findings can inform the development of effective strategies to combat the informal economy. For instance, strategies such as enhancing social support, increasing the freedom index, and combating corruption can potentially reduce the size of the informal economy and improve the overall economic situation in a country. Findings/Value – the research confirmed the hypothesis that the size of the shadow economy is smaller in countries with a higher happiness economy index. And Granger causality tests show that the shadow economy has a relatively strong effect on happiness in the EU euro area countries.